Pengaruh Permainan Playdough terhadap Kreativitas Anak di PAUD Al Muniri Wates: The Influence of Playdough Games on the Creativity of 4-5 Year Old Children at Al Muniri Wates Preschool - Rosi Alpiana; Hilmiati; Muhamad Harianto; Losi Wardani; Ozi Satria (Pendidikan Al-Gafari, 2025)
Early Childhood Education is a form of education that emphasizes laying the foundation for physical growth and development (fine and gross motor coordination), intelligence (thinking power, creativity, emotional intelligence, spiritual intelligence), socio-emotional attitudes and behaviors and religion), language and communication, in accordance with the uniqueness and stages of development that early childhood goes through. This study aims to analyze the effect of playdough game interactions on children's creativity at PAUD Al Muniri Wates. In this study, the method used is the experimental method. The data collection technique for this study is through documentation, observation and checklist techniques. The data analysis technique for this study is through data normality tests, homogeneity tests. Based on the results of the hypothesis test obtained through research on the effect of playdough games on children's creativity at PAUD Al Muniri Wates, based on the results of the research that the researcher has done regarding the results of calculations using SPSS by comparing the F value produced by the Fcount calculation with the Ftable value, the Fcount value is 6.860> Ftable value of 4.54, then Ho is rejected and Ha is accepted, which means that there is an effect of role play on children's interpersonal intelligence at PAUD AL Muniri Wates with a significance value of 0.000 <α value of 0.021. From the results of monitoring children's creativity abilities, it can be concluded that playdough games have an effect on children's creativity at PAUD Al Muniri Wates.